THE RELATIONSHIP BETWEEN VOCABULARY KNOWLEDGE AND LEARNING MOTIVATION TOWARD THE STUDENTS’ READING COMPREHENSION AT TADIKA PURI ELEMENTARY SCHOOL EAST JAKARTA - Mildan Arsdan Fidinillah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
The objective of this research is to investigate the relationship between vocabulary knowledge and learning motivation toward the students’ reading comprehension. The instruments include one questionnaire and two tests distributed to analyze the data quantitatively. In conclusion, this research found to both vocabulary knowledge (X1 ) and learning motivation (X2) contributed the reading comprehension (Y). In other words, the more vocabulary the students have and the more their motivation in learning, the greater they comprehend the text would be. As a consequence, it suggests that the teachers teach the appropriate vocabulary to the students where these vocabulary will help them in comprehending the reading text.Key words: Vocabulary knowledge, learning motivation, students’ reading comprehension